2000
DOI: 10.1287/isre.11.4.418.11876
|View full text |Cite
|
Sign up to set email alerts
|

Research Report: The Evolving Relationship Between General and Specific Computer Self-Efficacy—An Empirical Assessment

Abstract: The concept of computer self-efficacy (CSE) recently has been proposed as important to the study of individual behavior toward information technology. This paper extends current understanding about the concept of self-efficacy in the context of computer software. We describe how two broad types of computer self-efficacy beliefs, general self-efficacy and task-specific self-efficacy, are constructed across different computing tasks by suggesting that initial general CSE beliefs will strongly predict subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
358
4
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(395 citation statements)
references
References 40 publications
25
358
4
8
Order By: Relevance
“…In fact, e-government offers substantial performance gains over the traditional model of government. For example, based on the analysis of 49 1 Gulf University for Science and Technology, West Mishref, Kuwait, e-mail: moustafa.m@gust.edu.kw IN EGYPT VIA DATA MINING TECHNIQUES 87 empirical studies, Danziger and Andersen (2002) concluded that there were positive egovernment impacts on data access and efficiency and productivity of government performance in both internal operations and external service functions. In fact it has been argued that a significant portion of the benefits created by e-government services are obtained by the government itself in terms of efficiency gains (Tung and Rieck, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, e-government offers substantial performance gains over the traditional model of government. For example, based on the analysis of 49 1 Gulf University for Science and Technology, West Mishref, Kuwait, e-mail: moustafa.m@gust.edu.kw IN EGYPT VIA DATA MINING TECHNIQUES 87 empirical studies, Danziger and Andersen (2002) concluded that there were positive egovernment impacts on data access and efficiency and productivity of government performance in both internal operations and external service functions. In fact it has been argued that a significant portion of the benefits created by e-government services are obtained by the government itself in terms of efficiency gains (Tung and Rieck, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While this view was obtained under the context of game-based virtual training, this attitude would likely be transferrable for other virtual training which involved low-level computer self-efficacy. Computer self-efficacy (or perceived computer self-efficacy), which refers to an individual's judgement of his her ability to use a computer (Compeau and Higgins, 1995), and computer anxiety are important determinants in influencing an individual perception of a technology's ease of use and acceptance (Agarwal, et al, 2000). Existing virtual environment usability criteria (Stanney et al, 2003;Gavish et al, 2011) could be used to assist decisions regarding user interface design of virtual training.…”
Section: Discussionmentioning
confidence: 99%
“…They assumed that a person at a high level of personal innovativeness might be a risk-lover or early adopter, so that personal innovativeness affects the user's behavior or intention to use the new technology. Agarwal et al [66] determined too that personal innovativeness with information technologies affects beliefs about general and specific computer self-efficacy, and has a positive effect on perceived ease of use. In conclusion, as prior research demonstrates, we find that innovativeness is significant in using ubiquitous computing services in urban environments.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy has been widely used in explaining individual differences [64][65][66][67]. Bandura [68] mentions that self-efficacy is the belief in an individual's capabilities to organize and execute a specific task, required to produce given attainments.…”
Section: Agarwal and Prasadmentioning
confidence: 99%
See 1 more Smart Citation